The usability of a virtual reality augmented training program to teach goniometry to occupational therapy students - Nancy A. Baker; Jane O’Shanassy; Carolyn A. Unsworth (BMC Medical Education, 2025)
Abstract Background Training occupational therapy students in manual skills such as goniometry typically requires intensive one on one student teacher interactions and repetitive practice to ensure competency. There is evidence that immersive virtual reality (IVR) supported embodied learning can improve confidence and performance of skills. Embodied learning refers to learner’s experience of viewing a simulated body and its properties as if they were the learner’s own biological body. The aim of this proof-of-concept study was to develop and examine the usability and establish preliminary efficacy of an Embodied Goniometric Occupational Therapy Training Program (EGOTTP) to teach occupational therapy students wrist goniometry. Methods Following the generation of written scripts, we used a 360-degree camera to film and create the program, with 3- levels of detailed education for six wrist goniometry measures, flexion-extension, radial-ulnar deviation and pronation-supination. Five students rated their experience using EGOTTP on measures of usability and efficacy. Results The EGOTTP was developed over a 1-month period, and the participants reported good to high levels of embodiment and engagement, and their ratings suggested that the EGOTTP was easy to use with the support of an educator. Conclusion IVR training programs such as this one hold promise for teaching manual skill acquisition such as goniometry. As IVR technologies become more affordable and widespread, this approach could complement other strategies used to teach goniometry skills to students.